[OP.5C.04] CENTRAL SYSTOLIC BLOOD PRESSURE AND CENTRAL PULSE PRESSURE PREDICT LEFT VENTRICULAR HYPERTROPHY AND SUBCLINICAL ARTERIAL INJURY IN HYPERTENSIVE CHILDREN. (September 2017) - Obrycki, L.; Niemirska, A.; Kulaga, Z.; Litwin, M.
Abstract : Objective: Central systolic (cSBP) and pulse pressure (cPP) are better determinants of cardiovascular risk than brachial blood pressure. There are only few reports on use of cSBP and cPP in diagnostic approach to hypertensive children. We analysed utility of cSBP and cPP in diagnostic approach in hypertensive children. Figure. No caption available. Design and method: In 233 children (54 girls; 14.9 ± 2.6 years) referred with arterial hypertension diagnostic process including assessment of 24 hour ABPM, left ventricular mass index (LVMi), carotid intima-media thickness (cIMT), pulse wave velocity (PWV), cSBP and cPP was done. PWV, cSBP and cPP were assessed using oscillometric device (Vicorder®). Results: 108 subjects had white coat hypertension (WCH), 21 ambulatory prehypertension (ambpreHT), 33 ambulatory hypertension (ambHT) and 71 severe ambulatory hypertension (severeHT). The groups didn't differ regarding age and sex distribution. In all hypertensive children primary hypertension was ultimately diagnosed. cIMT, LVMi, PWV, cSBP and cPP increased across blood pressure strata from WCH to severeHT with differences found between severeHT and WCH patients regarding cIMT (0.46 ± 0.04 mm vs 0.44 ± 0.03 mm; p = 0.004) and cSBP (120 ± 10 mmHg vs 114 ± 9 mmHg; p = 0.017). Patients with severeHT had greater cPP (51 ± 9 mmHg) in comparison with WCH (47 ± 9 mmHg; p = 0.009) and ambpreHT patients (44 ± 6 mmHg; p = 0.017). LVMi and cIMT correlated with cSBP (r = 0.220; p = 0.0007 and r = 0.14; p = 0.04, respectively) and cPP (r = 0.274; p = 0.0001 and r = 0.202; p = 0.002, respectively). 36 patients with left ventricular hypertrophy (LVH) had greater cPP (52 ± 10 mmHg) in comparison with subjects without LVH (47 ± 8 mmHg; p = 0.027). Regression analysis revealed cPP as the only predictor of LVMi (r2 = 0.09, B = 0.143, p = 0.03). ROC area for predictors of LVH revealed similar area under curve for cSBP (0.585), sPP (0.618) and 24 h systolic blood pressure (0.612). Conclusions: cSBP and cPP differentiates patients with severeHT and TOD from patients with WCH, ambpreHT and ambHT without TOD.